2021
DOI: 10.15252/embj.2020107294
|View full text |Cite
|
Sign up to set email alerts
|

Phospho‐regulation, nucleotide binding and ion access control in potassium‐chloride cotransporters

Abstract: Potassium-coupled chloride transporters (KCCs) play crucial roles in regulating cell volume and intracellular chloride concentration. They are characteristically inhibited under isotonic conditions via phospho-regulatory sites located within the cytoplasmic termini. Decreased inhibitory phosphorylation in response to hypotonic cell swelling stimulates transport activity, and dysfunction of this regulatory process has been associated with various human diseases. Here, we present cryo-EM structures of human KCC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 69 publications
3
40
0
Order By: Relevance
“…The KCC3-PM mutant demonstrated more dynamic conformational changes within the ß7 strand and in the α8 and α10 helices (Chi G. et al, 2021). Multiple conformations for α7 were observed, in which the end of α7 moves 21 • outward entailing conformational changes in the α7/ß6 loop (Chi G. et al, 2021). Cryo-EM identified also two conformational states in KCC1, as α8 was observed either above or below α10 (Chi G. et al, 2021).…”
Section: Phosphorylation Affects Conformation Of Nkccs and Kccsmentioning
confidence: 94%
See 2 more Smart Citations
“…The KCC3-PM mutant demonstrated more dynamic conformational changes within the ß7 strand and in the α8 and α10 helices (Chi G. et al, 2021). Multiple conformations for α7 were observed, in which the end of α7 moves 21 • outward entailing conformational changes in the α7/ß6 loop (Chi G. et al, 2021). Cryo-EM identified also two conformational states in KCC1, as α8 was observed either above or below α10 (Chi G. et al, 2021).…”
Section: Phosphorylation Affects Conformation Of Nkccs and Kccsmentioning
confidence: 94%
“…To examine the effect of phosphorylation on structural organization, two different KCC3 mutants were generated with triple substitutions of Ser 45 , Thr 940 , and Thr 997 by either aspartate (KCC3-PM) or by alanine (KCC3-PKO). Analysis by cryo-EM revealed that the "dephosphorylated" KCC3-PKO is more dynamic in the scissor helix region and exhibits a greater rotational flexibility of the C-terminal dimer (Chi G. et al, 2021). The KCC3-PM mutant demonstrated more dynamic conformational changes within the ß7 strand and in the α8 and α10 helices (Chi G. et al, 2021).…”
Section: Phosphorylation Affects Conformation Of Nkccs and Kccsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoinhibition by disordered terminal domains has also been visualized directly in several potassium-chloride symporters [57,58]. In other transporters, such as eukaryotic NSSs, disordered termini instead regulate transport by interacting with a range of cytoplasmic proteins and lipids [93,94].…”
Section: Structural Diversity Outside the Ten-helix Corementioning
confidence: 99%
“…Interactions of KCC2 CTD with Protein Associated with Myc (PAM) [16] and PACSIN1 [17] regulate KCC2 expression positively and negatively, respectively, and affect KCC2-mediated ion flux accordingly, while its interactions with 4.1N [8] and β-PIX [18] are critical for proper dendritic spine formation. Recently, cryo-EM structures of different KCCs were solved, showing an inward-open conformation of the TM domain in each structure [19-24]. Those structures also revealed binding sites for K + and Cl - with highly conserved residues coordinated to those ions.…”
Section: Introductionmentioning
confidence: 99%